‘언어생활과 한자’의 문식성 교육 적용 담론 - 이성형 (동양한문학연구, 69(0), 2024)
본고는 2022 개정 한문과 교육과정의 신설 과목인 ‘언어생활과 한자’의 문식성 교육 적용 방안을 살펴보았다. 문식성은 디지털 전환에 따라 텍스트 개념의 확장으로 복합양식 문식성으로 규정된다. 한문과 문식성은 “한자․한자 어휘․한문과 관련된 모든 분야와 맥락에서 시각․청각 및 디지털 자료를 사용하여 식별․이해․해석․생성 및 의사소통할 수 있는 종합적인 능력”으로 정의할 수 있고, 한문과 문식성 교육은 ‘읽기’와 ‘쓰기’가 중심이 된다. ‘언어생활과 한자’ 교육과정의 ‘성격’과 ‘목표’는 어휘 수준의 문식성 역량 배양을 근간으로 하고 있다. ‘성취기준’은 원활한 언어생활, 인성 함양, 한자 문화권 교류와 관련된 문식성 교육 요소를 반영하였다. ‘언어생활과 한자’의 문식성 교육을 적용하기 위해서 먼저 한문교육용 기초한자를 코퍼스 데이터 분석 결과를 참고하여 사용 빈도와 위계를 고려하여 재선정해야 한다. 다음으로 ‘언어생활과 한자’ 문식성 교육 관련 적용 담론은 주로 한자와 한자 어휘에 대한 지식과 이해를 언어생활에 활용하는 방법론이다. 2015·2022 개정 교육과정에서 제시한 교수·학습 방법이나 문제중심학습법(PBL), 인공지능 원리나 기술을 응용한 교수·학습 방법과 함께 학업성취도와 어휘력 신장에 통계적으로 유용성이 검증된 ‘형태소 인식력’을 기르고, 이를 맥락 이해와 비판 능력에 활용할 수 있는 LBH 교수·학습 방법도 효과적이라고 판단된다. 한자 어휘에서 한자 형태소의 특징과 역할을 귀납적으로 분석하거나 단문과 장문 및 복합양식 텍스트에 사용된 한자와 한자 어휘를 맥락적으로 이해하고 분석하는 하향식 교수·학습 방법은 아직 일반적이지 않다. 맥락적 상황을 바탕으로 ‘한자·일상용어·학습 용어’의 형태소 인식력을 높일 수 있는 하향식 교수·학습 방법은 다른 교과와의 융합 수업에도 자연스럽게 연계될 수 있을 것으로 판단된다. This paper examined the application of literacy education for ‘Language Life and Chinese Characters’, a new subject in the 2022 revised Chinese character curriculum. Literacy is defined as multi-modal literacy as an expansion of the concept of text following digital transformation. Chinese character literacy can be defined as ‘the comprehensive ability to identify, understand, interpret, create, and communicate using visual, auditory, and digital materials in all fields and contexts related to Chinese characters, Chinese character vocabulary, and Chinese characters.’. Education in Chinese characters and literacy focuses on ‘reading’ and ‘writing.’ The ‘nature’ and ‘goals’ of the ‘Language Life and Chinese Characters’ curriculum are based on literacy competency education at the vocabulary level. The ‘achievement standards’ reflected literacy education elements related to smooth language life, character development, and exchange of Chinese character culture. In order to apply the literacy education of ‘Language Life and Chinese Characters’, the basic characters for Chinese character education must first be reselected by referring to the results of corpus data analysis and considering the frequency of use and hierarchy. Next, research on ‘language life and Chinese character’ literacy education is mainly a methodology that utilizes knowledge and understanding of ‘Chinese characters’ and ‘Chinese character vocabulary’ in language life. Teaching and learning methods proposed in the 2015·2022 revised curriculum, problem-based learning (PBL), and teaching and learning methods that apply artificial intelligence principles or technologies are effective. The LBH teaching and learning method is also effective in cultivating ‘morphological awareness’, which has been statistically proven to be useful, and using it for context understanding and critical skills. Top-down teaching and learning methods that inductively analyze the characteristics and roles of Chinese character morphemes in Chinese character vocabulary and contextually understand and analyze 'Chinese characters' and 'Chinese character vocabulary' used in short, long, and complex text are not yet common. not. A top-down teaching and learning method that can increase morphological awareness of ‘Chinese characters, everyday terms, and learning terms’ based on contextual situations can be naturally linked to convergence classes with other subjects. KCI Citation Count: 0